Raw Material Inventory Planning And Control To Achieve Inventory Cost Efficiency Case Study At PT. "X" In Surabaya - Lailatul Chamdiyah; Diana Zuhroh; Tjandra Wases; Sutini Sutini; Heri Toni Hendro P (Jurnal Mahasiswa Manajemen dan Akuntansi, 2023)
Raw materials are something that is very important for companies, especially for the production process. Overstock results in high costs of purchasing, storing and maintaining in warehouses. Meanwhile, outstock results in the cessation of the production process which causes large losses to the company because it cannot order sales. Therefore, to maintain the smooth production process, a planning and control of raw materials is needed, namely by using the EOQ (Economic Order Quantity) method as a means to solve raw material problems that are fulfilled. Case study at PT. “X” indicates that the company experienced overstock of Curcuma Rhizoma raw materials which resulted in high inventory costs for Curcuma Rhizoma amounting to IDR 7,742,469 and for Mellaleuca Fructus IDR 12,116,880. From the discussion it can be concluded that inventory management with the EOQ method. and raw material inventory control becomes more efficient so that the company can provide adequate raw materials to smooth the production process. This study shows that there is a significant difference if the company applies the EOQ method, in which the company can save costs of Rp.